Acesso à justiça : a análise da possibilidade de realização da arbitragem pela Defensoria Pública da União - Cavalcanti, Ricardo Russell Brandão (2011)
The judiciary is seen as the main form of conflict resolution, and because of this, is experiencing a crisis due to the excess processes. It turns out that there are other means of peaceful conflict resolution and other legal institutions that may be ahead of the resolutions of disputes. One such institution is the Public Defender of the Union. So, this study search through sought doctrinal and field study demonstrate that the Board Defensorial can collaborate with the Federal Judiciary and the whole community being forward of one of these institutes peacemakers: the arbitration. The choice of the Public Defender of the Union and not only for all of them aimed to facilitate the field research. So, the first chapter of this study focused on the conceptualization of the term "justice access," passing by the problematic term "justice" too. Then the barriers of justice access were analyzed until the Mauro Cappelletti and Bryant Garth renovations. In the second chapter come up through the systematic justice access guaranteed by the state, moment when studied and distinguished institutes of free justice, the Legal Assistance free and judicial assistance free. The third chapter is concerned in public defender institution, distinguishing the state branch of the federal branch and analyzing the functions and characteristics of this legal institution in many spheres. The fourth chapter brought the arbitration institution, its concept, its legal status, its procedure, its advantages, its importance, the nullity and how to choose that. In the fifth and final chapter expounded the possibility of carrying out the arbitration by the Public Defender of the Union, a brief overview on the judiciary crisis and then analysis of several questions about the arbitration conduct by the Public Defender of the Union, namely: probable impossibility of arbitration by a legal entity; the reliability factor; the labor causes questions; the nullity declaration point; the agreements with the government situation and, consequently, the arbitration by the latter option. The arbitration conducted by the Public Defender of the Union as an option for resourcepoor came about and then approached about the Public Defender of the Union experience in extrajucial resolution and arbitration specifically. At the end, it follows that the arbitration conducted by de Public Defender of the Union is a viable option and could contribute to de justice access, provided that a series of measures happen, such as The Public Defender of the Union strengthening